What is a print? : selections from the Museum of Modern Art - Suzuki, Sarah J. S.; Museum of Modern Art (New York, N.Y.) (New York : Museum of Modern Art, 2011)
What is a print? This volume aims to answer that question by exploring the four basic printmaking techniques--woodcut, intaglio, lithography and screenprint--that have been used to create some of the most iconic images in modern art, from Paul Gauguin's Noa Noa to Andy Warhol's Marilyn Monroe. Illustrated with works from The Museum of Modern Art's superlative collection of prints, the book is divided into four sections that provide an overview introduction to each technique. Each section presents approximately 40 prints that demonstrate the range and variety of a particular technique and illustrate its development over the last century. Extended captions highlight the distinctive visual effects unique to each technique, and examine issues specific to printmaking, such as democratic ideas about distribution and social and political function. Featured works range from Edvard Munch's radical woodcut experiments from the 1890s to Kelley Walker's digital experiments of the last several years, and include prints by modern masters like Pablo Picasso and Joan Miró as well as those made by a roster of international contemporary artists who continue to explore and expand these techniques today. -- Book Description.
Woodcut -- Intaglio -- Lithography -- Screenprint -- Other processes and new technologies.
Includes bibliographical references (page 166)
Keywords: Museum of Modern Art (New York, N.Y.) -- Catalogs; Prints -- 20th century -- Catalogs; Prints -- 21st century -- Catalogs; Prints -- 19th century -- Catalogs; Prints -- Technique; Prints -- New York (State) -- New York -- Catalogs; Prints -- 21st century